Determination of the Dielectric Loss Factor of a Grain-Air Mixture of Wheat - Dmitriy A. Budnikov (Сельскохозяйственные машины и технологии)
Abstract. The paper presents the data on the energy intensity of the heat treatment of grain during post-harvest processing caused by both the cost of energy and the grain moisture content. The development of processing modes using electrical technologies, in general, and electromagnetic fields, in particular, can make it possible to reduce the cost of these processes. Heat treatment is applied to the grain of various crops at the stages of drying, disinfection, preparation for feeding, etc. When developing them, it is necessary to take into account the types of applied electrical technologies, such as, for example, infrared fields, microwave fields, etc. (Research purpose) To determine the dielectric properties (dielectric loss coefficient) of a wheat grain-air mixture with a moisture content of 11-30 percents with a layer density of 220-660 kilogram per cubic meter. (Materials and methods) The authors present a diagram of a laboratory installation, carried out experimental studies to determine the dielectric loss coefficient of a fluidized bed of wheat grain. (Results and discussion) The authors conducted a two-factor experiment to determine the effect of moisture and density of a grain bulk on the dielectric loss factor, which determines the power absorbed from the microwave source. As a result, they obtained the studied relationships. (Conclusions) It was found that the dielectric loss coefficient at a grain moisture content of 11-30 percents is in the range of 0.18-0.42 for a dense grain bed of 660 kilogram per cubic meter, 0.06-0.15 for a fluidized bed (440 kilogram per cubic meter); and for a weighted bed (220 kilogram per cubic meter) 0.1-0.3. The authors calculated a dependence of the dielectric loss coefficient of a wheat grain-and-air layer on the grain moisture content and the layer density, which can be described by a polynomial model of a second power. The study showed that fluidization of the grain bed increases the efficiency of the microwave field, as due to a decrease in the dielectric loss coefficient, the depth of field penetration into the layer increases. It is recommended to use the microwave field in a dense bed of grain when drying wheat, thus reducing moisture from 16 to 14 percent.